ANALISIS ALIRAN INVESTASI DAN PERDAGANGAN PARIWISATA INDONESIA - Faurani I Santi Singagerda; Rina Oktaviani; Dedi Budiman Hakim; Reni Kustiari (Bina Ekonomi, 2013)
Tourism is one of the most significant contributors to the construction sector in Indonesia, with the contribution around 13.9 percent of the total GDP in 2012. In connection with the government's efforts in improving the contribution of tourism in an effort to boost economic growth while improving the welfare of society, then the increase in tourism investment as focus in the development program, the goal for the activities can provide added value as well as lead to increased production that will be produced. If it is known that the average investment for the tourism sector is Rp. 2.73 billion during the period 2006-2012. This figure also shows that the contribution of tourism investment to total investment amounted to only 6 percent (Kemenpraf, 2012), in other words, an investment in the tourism sector has not been able to provide optimal contribution to the national economy development. Based on the fact that some of the problems arising from the government's efforts to boost trade and investment in the tourism sector continues to be done. The determinant factors of the amount of investment and trade from the Indonesian tourism and other countries to be considered and used as the basis of decision-making reference. Similarly, the amount of trade and investment flows to and from outside the State, are also worthy of consideration. To answer the problems, we use the gravity model as methodology and construvt the model of investment and trade of flows which consists of 5 models: the model of the flow of Indonesian tourism investment, exports of goods and services models Indonesian tourism, imports of goods and services model of tourism in Indonesia, Indonesian tourism demand flow model, and the model Indonesian tourism supply. Based on the results of the analysis using the five models were obtained magnitude of investment inflows to Indonesia influenced by the population of the country of origin of tourists and mileage of the country of origin of foreign tourists to Indonesia, where the influence of explanatory variables endogenous variables as a whole is at 0:42 at a significance level of 95 percent. The magnitude of the flow of goods and services exports of Indonesian tourism is affected by the distance variable, price of Indonesian tourism in the country of origin of tourists, exchange rate against foreign currencies origin of tourists, population, tourism and exports of the previous year are variables that significantly affect the confidence level of 95 percent, the magnitude of the effect was 92.7 percent and this shows considerable influence.In the model the flow of goods and services for Indonesian tourism, we use a variable distance, Indonesian GDP, the exchange rate, the price of Indonesian tourism in the countries of origin of tourists and imports of goods and services in the Indonesian tourism previously an influential variable significantly (at 90 percent confidence level), and in general of the statistical results obtained by the relationship between the value of imports of goods and services to the Indonesian tourism is the independent variable by 96 percent. In the model flow of Indonesian tourism demand, the estimation results indicate that the tourism demand variable by independent variables Indonesian GDP, GDP of the country of origin of tourists, tourism for Indonesia, Tourism for the competing countries of ASEAN countries, and tourism consumption by foreign tourists in Indonesia as significant variables in the real level of 0:05 with the magnitude of the effect is at 93.2 percent. Statistically, the result also define there is relationship between magnitude supply of Indonesian tourism deals with variable-GDP Indonesia, Indonesian tourism price, exchange rate, domestic consumption, and consumption in other countries as variables significant (at significance level 0.05) effect on variable deals with the influence of Indonesian tourism amounted to 95.6 percent and the remaining 4.4 percent are influenced by other factors outside of the study such as inflation, interest rates, and investment tourism.